PENENTUAN KUALITAS DEGUMMED BLEACHED PALM OIL (DBPO)DAN REFINED BLEACHED DEODORIZED PALM OIL (RBDPO) DENGAN PEMBERIAN BLEACHINGEARTH PADA SKALA INDUSTRI - Hesty Heryani JTIP (Jurnal Teknologi Industri Pertanian, 2019)
Bleaching earth is a material absorbing various impurities bounded during the degumming process. Its other function is as CPO colour bleaching material in bleaching process. The study was conducted to determine the efficiency of the production process at the best concentration of giving bleaching earth toquality of degummed bleached palm oil (DBPO) and refined bleached deodorized palm oil (RBDPO), during fractionation. The quality parameters observed were free fatty acid (FFA), colour, cloud point and iodine number. The use of earth bleaching concentration ranges was set from 0.6% to 1.0%. Production process efficiency was measured on the basis of maximum RBDPO output and minimum input at a capacity of 2,000 tons per day with a flow rate of 41.6 t/h. The best results were obtained with FFA DBPO values of ≤ 4.5%, FFA RBDPO of 0.051% - 0.053%, colour of DBPO of 19R-21R, colour of RBDPO 2.25R-2.70R, the use of bleaching earth 0.8% - 0.9%. At this concentration cloud point DBPO was 2.15 ppm and 1.95 ppm. For the RBDPO cloud point at the same bleaching earth, the concentration was 2.47 and 1.76 ppm. The measurement results of iodine value were at 51,794 mg I2/g to 52,775 mg I2/g, meaning the value was still in the industry RBDPO quality standard of 50 - 55 mg I2/g. Addition of 0.8% - 0.9% bleaching earth could maintain the quality of DBPO and RBDPO with the efficient production process reaching 95.51%.Keywords: cloud point, degumming, flow rate ,free fatty acid, iodine number